Involvement Of Inula Racemose Hook Extract on Ischemic Preconditioning Mediated Cardioprotection in Diabetes - Tiwari, Arun Kumar; Gupta, Pushpraj S; Prasad, Mahesh (International Journal of Membrane Science and Technology, 2023)
Objective: Ischemia of the heart is one of the major cause behind diabetes mediate death in peoples. PI3K/Akt phosphorylation is inhibited in IPC-induced infarcts, preventing the opening of the mitochondrial permeability transition pore (MPTP). In diabetics, the beneficial effects are lessened. IPC-mediated cardioprotection in diabetic Wistar rat hearts was observed in this study after pre-treatment with Inula racemosa Hook root extract (IrA). Ischemia reperfusion (I / R) and cycles of IPC were performed on an isolated rat heart mounted on Langendorff’s assembly. MPTP is opened by atractyloside (ATR). Method: RP-HPLC and 1H and 13C NMR were used to identify the chemical components. Western blot, oxidative stress, mitochondrial function, integrity, and haemodynamic parameters are all examined in this study. Result: Pretreatment with IrA reduced LDH, CKMB, myocardial infarction size, ventricular fibrillation, and cardiac collagen content, as well as decreased oxidative stress levels and mitochondrial dysfunction in diabetic rat hearts in all groups, according to the data. By blocking the opening of MPTP in diabetic rats, ATR reduced the cardioprotective effect of IrA on IPC. Conclusion: This shows that IPC-mediated cardioprotection can be restored by pre-treatment with IrA, which inhibits the opening of the MPTP in diabetic rats.